Penerapan Clustering dalam Data Science Untuk Mengembangkan Keterampilan Analitik di SMK Media Informatika - Eliyani, Eliyani; Rifqi, Muhammad; Dwiasnati, Saruni (Unity Academy, 2024)
The current and future job market requires a workforce skilled in data science, including analytical techniques such as clustering. With the development of Industry 4.0, skills in data analysis are becoming increasingly important, and education must adapt to meet this need. Currently, there are still many students at the vocational high school level who do not understand the concept of data science, including clustering techniques, so they have difficulty understanding how data can be generated for decision making from each scheme. The method that can be used in this Community Service is an introduction to the basic concepts of data science and simple training in the use of simple data science tools. The goal that can be raised for the Community Service that we do is to provide students with a basic understanding of what data science is as one method for making important data decisions. The contribution that can be generated from the Community Service that we do is that students will have basic skills in knowledge related to data science, especially in understanding and applying clustering techniques for data analysis. The result of the Community Service that we do is that students understand the basic concepts of data science and clustering and how this method is applied in the analysis of the data obtained.